Strategi Komunikasi Pemasaran: Pengaruh Advertising, Endorsement, dan Brand Image terhadap Loyalitas Konsumen Telkomsel - Ismi Iftikad; Kirana Putri Pratama (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
This study aims to analyze the effect of Advertising, Endorsement, and Brand Image on Telkomsel Customer Loyalty. A quantitative explanatory research design was employed. The sample consisted of 100 respondents determined using the Lemeshow formula with purposive sampling criteria, namely Telkomsel users aged at least 17 years and having used the service for a minimum of one year. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS.The results indicate that Advertising and Brand Image have a positive and significant effect on Customer Loyalty, while Endorsement does not have a significant partial effect. Simultaneously, the three variables significantly influence Customer Loyalty with a contribution of 37.4%. Brand Image is identified as the most dominant variable affecting customer loyalty.These findings suggest that in the telecommunications industry, customer loyalty is more strongly influenced by brand perception and service quality image rather than celebrity endorsement appeal.